ANALISIS PENGENDALIAN KAS PADA KOPERASI UNIT DESA SANGATTA - -, Indra Samudra (EKONOMIA, 2015)
The research problem is, did the cash control system and procedures in KUD Sanggatta has met internal control system or not. The basic theory of this are Accounting Systems, Internal Cash Control, and Cooperative. Proposed hypothesis is cash control procedures and systems at KUD Sangatta has met the internal control system.The analytical tool used to analyze the system and cash control procedures are comparative method (comparison), which compares the internal control system used by KUD Sanggatta with the internal control system according to the literature by using a flowchart (flow chart) . And comparing between flow chart according to the theory with the flow chart existed inÂ  KUDSangatta.Based on the analysis and discussion that has been presented in the previous chapter towards the hypotheses that have been proposed by the authors it is alleged that, cash control procedures and in systems Sangatta village unit cooperation (KUD) have met the internal control system, proven or accepted based on :KUD Sanggatta in managing cash control procedures and systems have designed a system of cash receipts that involving all elements which are the owners, management and debtor of the KUD Sangatta own.Cash control procedures and systems in KUD Sangatta has met the elements of the internal control system, but need to be noted, it is necessary to periodically do cash reconcile with cash control account in the general ledger.Systems and cash control procedures in KUD Sangatta could be regarded as a system of control for the systems and procedures implemented have been describe the existence ofÂ  forms organizing, records, and reports are coordinated so as to provide the financial information required by management in order to facilitate the company activities management.Cash control procedures and systems in KUD Sangatta been equal with the actual control procedures and system according to the theory.So, the previously proposed hypothesis that it is alleged that, cash control procedures and systems in KUD Sangatta have met the internal control system, proven or accepted because it turns out the cash accounting system and procedures at KUD Sangatta already met the internal control system.